Responsibility for Beliefs and Emotions - McCormick, Miriam; Schleifer, Michael (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2006)
This paper maintains that the concept of responsibility must be extended to beliefs and emotions. It argues that beliefs and emotions have their crucial link through the element of judgment. Judgment refers to relationships in contexts of ambiguity and uncertainty; developing good judgment in children involves the question of similarities and differences in varying situations and contexts. Both beliefs and emotions are crucial to this process. Educators interested in helping develop better judgment must look at the relevant beliefs and emotions associated with the judgments we make. Just as children must be made aware of their responsibility for behaviour, so must they understand that they are responsible for their beliefs and emotions.